Ideological Polarization and Satisfaction with Democracy in Latin America: a Controversial Link - Barreda Díez, Mikel; Ruiz Rodríguez, Leticia M. (Revista del CLAD Reforma y Democracia, 2020)
Ideological polarization is a crucial aspect of party systems that varies over time and between party systems. Experts have tended to highlight its negative effect. This article proposes an alternative view, focusing on a possible positive effect, by relating polarization to the existence of differentiated ideological options that would increase the inclusiveness of the party system as a whole and make a positive contribution to satisfaction with democracy. With polarization data calculated from the positions of the parliamentary elites of sixteen party systems, the analysis addresses the relationship between polarization and the quality of democracy. The result suggests the relevance of this relationship and the need to reconsider the mechanical interpretation of the negative effects of polarization.
Keywords: Democracy; Political Party; Political Analysis; Latin America